SAUDI ARABIA'S INTEREST IN YAMAN CONFLICT (2011-2015) - Daulay, M. Habib akbar; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is a diplomatic and strategic political study which describes Saudi Arabia's interests in helping the conflict in Yemen. This study is describing about the Saudi Arabia’s government role in middle east. Saudi Arabia’s government have to make the conflict in Yemen stable and not disturbing the security around the Middle East.This is qualitative research which used descriptive methods, and collecting datas from some resources like books ,journals, official publications, and any relevant websites. This paper uses a Neorealist perspective and the Alliance Theory from Stephen Walt. The object of this research is Saudi Arabia which is the main actor in International Relations.          The results of this study indicate that Saudi Arabia took several actions to assist the Yemeni government in dealing with conflicts. Saudi Arabia as the Chairperson of the Union of Middle Eastern countries formed a coalition to fight the insurgency in Yemen. Saudi Arabia also provides direct military assistance to the Yemeni government by sending weapons and other military supports. Saudi Arabia is also forming a coalition with the United States to help them fight rebels in Yemen backed by Iran. Keywords: Aliance, Weapons, Conflict, Military